Risk factors for adverse maternal and fetal outcomes in SLE patients: a systematic review and meta-analysis - Liu, Hang; Li, Meifei; Wang, Meijiao; Ren, Minzhe; Fu, Jiaying; Cai, Ying; Li, Zhiyu; Zhao, Ting; Sun, Jing; Xie, Zhijun (Frontiers in Medicine, 2025)
BackgroundSystemic lupus erythematosus (SLE) is a multisystem autoimmune disease that increases the risk of adverse maternal and fetal outcomes in SLE pregnancies. Identifying potential risk factors can enhance preconception risk assessment for SLE pregnancies, thereby reducing the burden of pregnancy for SLE patients.ObjectiveThe goal of this meta-analysis is to designate the risk factors for unfavorable maternal and fetal outcomes in SLE pregnancies by means of a systematic review of the literature and meta-analysis.MethodsThe odds ratios (ORs) and associated 95% confidence intervals (CIs) were estimated using either a fixed-effects model or a random-effects model. The I2 statistic was used to assess heterogeneity. Sensitivity analysis, Egger’s test, the Newcastle-Ottawa Quality Assessment Scale (NOS), and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system were also performed.ResultsEleven papers with 1,790 SLE patients who were pregnant were examined in the meta-analysis out of 2,467 citations that were screened. The meta-analysis’s findings indicated that the onset of SLE is associated with an increased risk of preterm birth (OR: 2.85; 95% CI: 2.04, 3.99). Hypertension is associated with an increased risk of composite pregnancy outcomes (OR: 4.56; 95% CI: 2.42, 8.53), preterm birth (OR: 2.20; 95% CI: 1.53, 3.17) and preeclampsia (OR: 10.11; 95% CI: 1.83, 55.89). Renal involvement is associated with an increased risk of composite pregnancy outcomes (OR: 3.09; 95% CI: 1.66, 5.72) and preterm birth (OR: 1.65; 95% CI: 1.22, 2.23). Anti-dsDNA is associated with an increased risk of preterm birth (OR: 1.83; 95% CI: 1.13, 2.92) and pregnancy loss (OR: 2.64; 95% CI: 1.09, 6.40). Drug therapy is associated with a decreased risk of composite pregnancy outcomes (OR: 0.51; 95% CI: 0.31, 0.85), preterm birth (OR: 0.66; 95% CI: 0.48, 0.89) and pregnancy loss (OR: 0.42; 95% CI: 0.21, 0.84). Sensitivity analysis demonstrated how solid our results are. Egger’s test revealed no discernible publication bias.ConclusionThe onset of SLE, hypertension, renal involvement, drug therapy, and serological factors have a predictive effect on the occurrence of adverse maternal and fetal outcomes in SLE pregnancies. Strengthening preconception risk assessment for SLE patients plays an important role in reducing pregnancy risks and improving the quality of life during pregnancy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails, identifier: CRD42024564190.